Relación entre el consumo de micronutrientes durante el embarazo y la desnutrición crónica infantil: Un análisis para el caso ecuatoriano durante el periodo 2018. - Puchaicela Buri, Ruth Angela (2023)
In Ecuador, in 2018, 23% of children under five years of age suffer from chronic child malnutrition. The present research aims to determine in a statistical, econometric and qualitative analysis, the determinants of chronic child malnutrition for the Ecuadorian case during the period 2018. The National Health and Nutrition Survey (ENSANUT) 2018 data was used, with a discrete choice model and the elaboration of the logical framework analysis. Thus, it is found that the determinants of chronic child malnutrition are the low consumption of micronutrients (iron, folic acid) of the mother during pregnancy. Likewise, the rural area, adolescent women and the mother’s level of education are factors that have a significant result in this study. It is concluded that micronutrient intake during pregnancy is the basis for growth in children. Finally, it is recommended that the policy should strengthen health centers to include training among their activities, as well as the Autonomous Decentralized Governments at different levels, so that they can participate in the expansion of training and information corresponding to the Ecuador Grows Without Child Malnutrition plan, the subprogram called “Micronutrient Implementation Program” and the food guides, allowing households in different corners of the country to Access the benefits of this plan, mainly mothers or women with family planning.